Inverse nodal problem for singular differential operators - Koyunbakan, H. (My University, 2005)
Browne and Sleemens's paper is concerning the determination of potential uniquely from the nodes for regular sturm liouville problem. In this paper, we show that the potential function in the Sturm - Liouville problem having singularity at the point zero can be determined from the position of the nodes for the eigenfunctions. © VSP 2005.